The investigation of the market disequilibrium in the stock market - Park, Jin Suk (2013)
This thesis investigated stock market disequilibrium focusing on two topics: the impact of multiple market makers on the market disequilibrium at the market microstructure level, and the detection of the long-run market disequilibrium in the context of bubbles and the changes in transition probabilities.